Embedded Double One‐Dimensional Composites of WO3@N‐Doped Carbon Nanofibers for Superior and Stabilized Lithium Storage. Issue 2 (25th January 2022) - Yang, Jiaxuan; Du, Shenyu; Ao, Liyuan; Zhang, Jihao; Jin, Chunqiao; Han, Meijie; Jiang, Kai; Shang, Liyan; Li, Yawei; Zhang, Jinzhong; Zhu, Liangqing; Hu, Zhigao; et al.
Abstract: Tungsten oxide has received plenty of attention as a potential anode material for lithium‐ion batteries (LIBs) due to the high intrinsic density and abundant framework diversity. However, the tremendous structural and volumetric changes of tungsten oxide (WO3 ) restrict the commercial application. A novel embedded one‐dimensional (1D) structure composite of the WO3 and N‐doped carbon nanofibers (WO3 @N‐CNFs) has been prepared by combining convenient hydrothermal and electrospinning processes. The WO3 nanowires are firmly wrapped in the N‐CNFs and formed an embedded double 1D structure, which can significantly improve the structure stability of the composite. Therefore, the WO3 @N‐CNFs delivers a high specific capacity of 960 mAh/g after 300 cycles at 0.2 A/g, and 550 mAh/g after 1300 cycles at 2 A/g. Moreover, the initial Coulomb efficiency of WO3 @N‐CNFs is enhanced to more than 80 %. The electrochemical performance is better than those from most WO3 ‐based carbon composite materials, which can be ascribed to the synergy effects of the WO3 nanorods and the nitrogen doping in 1D carbon nanofibers. As a consequence, the WO3 @N‐CNFs can be a promising anode material with the extraordinary long‐term cycling performance at high current densities, and provide a new idea for the commercialization of WO3 ‐based carbon composite materials. Abstract : Double trouble : The double 1D composite of hydrothermal ultrafine WO x nanowires and electrospinning N‐CNF exhibits remarkably improved rate performance, long‐term cycling stability and electrical conductivity as anode material of advanced lithium‐ion batteries.